Novel bioresorbable textile composites for medical applications - Zhu, Chenkai; Ahmed, Ifty; Parsons, Andy J.; Wang, Yunqi; Tan, Chao; Liu, Jingsong; Rudd, Chris D.; Liu, Xiaoling (2017)
Currently, phosphate glass fibre (PGF) reinforced composites are a potential solution for bone repairing due to sufficient mechanical properties and full bioresorbability. In this study, a small inkle-type loom for hand weaving facilitated the production of PGF in textile form. These PGF textiles, along with unidirectional (UD) fibre mats made from the same batch of yarns, were utilised to manufacture fully resorbable textile composites (T-C) and 0°/90° lay-up UD fibre reinforced composites (0/90-C). Retention of flexural properties and weight loss of the composites were evaluated during degradation in phosphate buffered saline (PBS) at 37°C for 28 days. The initial flexural strength values that were observed for the T-C and 0/90-C composites were ∼;176 MPa and ∼;137 MPa, whilst the modulus values were 8.6 GPa and 6.9 GPa, respectively. The higher flexural strength and modulus values for the T-C when compared to those of 0/90-C were attributed to the textile weaving manually, resulting in a biased fabric with a higher density of fibres in the warp direction. ∼;20% flexural strength and ∼;25% flexural modulus were maintained for all composites at the 28 day interval. For this study, the textile achievement will be the significant milestone on the research of bioresorbable PGFs reinforced composite in medical application, and important step on the industrial direction of bioresorbable medical device. © 2017 International Committee on Composite Materials. All rights reserved.